2018
DOI: 10.5194/acp-2018-699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New particle formation in marine atmosphere during seven cruise campaigns

Abstract: Abstract. To study the particle number concentration, size distribution and new particle formation (NPF) events in marine atmosphere, we made measurements during six cruise campaigns over the marginal seas of China in 2011-2016 and one 10 campaign from the marginal seas to the Northwest Pacific Ocean (NWPO) in 2014. We observed relatively frequent NPF events in the atmosphere over the marginal seas of China, i.e., 23 out of 126 observational days with the highest occurrence frequency in fall, followed by sprin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 57 publications
4
23
1
Order By: Relevance
“…The fitted equation was highly consistent with those derived for urban and marine atmospheres (Man et al, 2015;Zhu et al, , 2019Ma et al, 2020). The strong linear relationship between the FR and NMINP suggested that H2SO4 vapor was sufficient for nucleation, and the NPF intensity was very likely determined by the abundance of organic vapors available for participating in nucleation.…”
Section: Table 2 Provides a Comprehensive Comparison Of The Measured supporting
confidence: 76%
See 2 more Smart Citations
“…The fitted equation was highly consistent with those derived for urban and marine atmospheres (Man et al, 2015;Zhu et al, , 2019Ma et al, 2020). The strong linear relationship between the FR and NMINP suggested that H2SO4 vapor was sufficient for nucleation, and the NPF intensity was very likely determined by the abundance of organic vapors available for participating in nucleation.…”
Section: Table 2 Provides a Comprehensive Comparison Of The Measured supporting
confidence: 76%
“…The increase in the NMINP should enhance the contribution of NPF events to the ambient particle number concentration, but the NMINP at Mt. Tai before 2015 was only approximately ¼-½ of our previous observations in urban and marine atmospheres (Zhu et al, , 2019.…”
Section: Variations In the Fr Nminp Gr And Dpgmaxcontrasting
confidence: 74%
See 1 more Smart Citation
“…Qingdao (Li et al, 2015a), Shanghai (Leng et al, 2013;Leng et al, 2014), Guangzhou (Duan et al, 2017;Duan et al, 2018) and Mt. Huang (Fang et al, 2016), as well as over marginal seas of China (Zhu et al, 2019; and northwestern Pacific (Wang et al, 2019a;Zhu et al, 2019). As these studies did not carry out size-resolved measurements and thus did not report critical diameters or κ, they are not further discussed herein.…”
Section: Ccn Activitiesmentioning
confidence: 99%
“…When released into the environment, they can be degraded by bacteria to trimethylamine (TMA) and then dimethylamine (DMA) or methylamines (MA) (Lidbury et al, 2015a;Lidbury et al, 2015b). Gaseous DMA, TMA, and MA may play an important role in the formation of secondary particles in the atmosphere by nucleation (Almeida et al, 2013;Chen et al, 2016;Yao et al, 2018;Zhu et al, 2019). However, measuring gaseous amines in real-time simultaneously to their particulate counterparts in the marine atmosphere over the ocean remains challenging, although this is not the case in the continental atmosphere (VandenBoer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%